Kekerasan dan Ketakutan pada Kekerasan - Suparman Marzuki (Universitas Islam Indonesia, 2006)
The social violence phenomenon can not be explained and related to the structural domains only, but it is also involved and influenced by social, political, law and that of politician and leaders behavior. In Western societies is not so urgent to relate the politician and the leaders behavior, but for Indonesian nation that of behavior is involved because social relation between leaders and their community sometimes supported and directed by social trust, instead that of spiritual. This relation has psychological dimension which can be stabilization and anarchy factors. In this respect, the role of law, law enforcement, the institution of law should be first priority to control, minimize violence, and fear of violence.